Application of a hybrid-fruit-peel (HFP) coagulant in low carbon source wastewater treatment as an external carbon source - Fu, Ying (Water science and technology : a journal of the International Association on Water Pollution Research, 2024)
The application of a hybrid-fruit-peel (HFP) coagulant used as an external carbon source (ECS) in both simulated water and real sewage having a low carbon source treated with sequencing batch reactor (SBR) was studied, compared with that of sodium acetate (NaAc). The impact of HFP on sludge properties (such as extracellular polymer substance (EPS), dehydrogenase activity (DHA), charged property, size, microscopic images and bacteria phase) was characterized. The results showed that as an ECS, HFP basically gave similar nitrogen removal to NaAc and also gave a similar developing trend of both dissolved oxygen (DO) and pH. HFP promoted more proliferation of microorganisms and posed higher levels of protein (PN) and polysaccharide (PS) than NaAc, but gave slightly lower DHA than NaAc. After HFP was added as an ECS, the types and quantities of microorganisms increased significantly, the effluent qualities were improved and the sludge size and extensibility became larger, which was conducive to direct contact and remove pollutants. HFP played a similar role to NaAc as ECS and can be used as a quality and slow-releasing ECS for low carbon source wastewaters